Role of Psychological and Pedagogical Support in the Life of People With Disabilities? - Ziętek Аnna (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The paper presents the essence and needs of support in the lives of people with disabilities. It shows that in order to adapt support to the individual needs of people with disabilities it is necessary to introduce elements improving the aid system. It indicates the tasks and importance of factors of the system supporting people with disabilities individually and in the social and professional environment. Legislative solutions in force were presented, which are aimed at stimulating professional activity and integrating disabled people and their families into the environment. The paper offers solutions to improve the system of equalization of opportunities in social and professional life of people with special needs. The importance of supporting professional activity and employment in the labour market was discussed. An attempt was made to assess the factors determining the effectiveness of the system, taking into account the implemented aid programs, grants, benefits and tasks of organizations and institutions supporting people with disabilities in social and professional life. The importance of integration, family support, support of the environment as well as adaptation of the system to the needs of people with disabilities was presented. Among the listed factors relating to people with disabilities, the importance of preparation, professional development and adaptation to the open labour market was presented. The social perception of disability is also of particular importance, which, if properly shaped, can reduce the problem of functioning of people with disabilities in social and professional life. People with disabilities show differing levels of need for safety, independence or accessibility to social infrastructure. This diversity depends on the support of families of people with disabilities, their caregivers and aid institutions and organizations, including those providing education, rehabilitation and vocational activity services. The paper presents activities, which are the starting point for looking for new solutions and improving current solutions for adapting support to the individual needs of people with disabilities